FARMERS’ PREFERENCES, SEED SOURCE, PRODUCTION CONSTRAINTS AND IMPROVEMENT NEEDS ASSESSMENT OF BAMBARA GROUNDNUT (VIGNA SUBTERRANEA [L.] VERDC.) IN NORTHERN RURAL OF NAMIBIA - Johanna Shekupe VALOMBOLA; Simon Kamwele AWALA; Kudakwashe HOVE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Bambara groundnut (Vigna subterranea [L.] Verdc.) is one of the neglected and underutilized legume crops grown by resource-poor smallholder farmers in sub-Saharan Africa (SSA). Its potential has been neglected for years by researchers and hence has remained an orphan crop. The objectives of this study were to assess preferences, seed availability, crop improvement needs and production challenges faced by Bambara groundnut farmers in Namibia. A cross-sectional survey comprising 100 randomly selected farmers was conducted in five of the eight northern regions of Namibia. Results showed that large seed size, cream seeds, early maturity, and drought-tolerant are the main farmer-preferred traits. Okaongoti was the most preferred (20%) variety. The primary seed sources are own saved seed (61%) and a combination of informal market and own saved seed (25%). The major production constraints of Bambara groundnut were insect pests, low yield and lack of improved varieties. Breeding of Bambara groundnut varieties with the farmer-preferred traits is vital to improving its yield level and overcome production challenges in the country.